Implementasi Projek Penguatan Profil Pelajar Pancasila di SMK NU 2 Kedungpring: Studi Kasus Tema Kewirausahaan - Soraya, Fadlilah Himmah; Abdillah, Muhammad Alfian Nur; Waidin, Zubdatul; Jannah, Arikhni Roikhatal; Zubaidah, Ayu Ainun; Al Maulidi, Abdullah Najib; Asrori, Muhammad (Innovative: Journal Of Social Science Research, 2025)
Entrepreneurship education at the vocational school level plays a crucial role in equipping students with skills relevant to the workforce while shaping character aligned with the noble values of the nation and religion. SMK NU 2 Kedungpring implements an entrepreneurship program as part of the Pancasila Student Profile Strengthening Project (P5), which aims to develop students' character through three main themes: entrepreneurship, sustainable living, and building both body and mind. There are three research focuses, namely, evaluating the implementation of the entrepreneurship program at SMK NU 2 Kedungpring, identifying its influence on the formation of students' Islamic character, and exploring the potential and challenges faced by schools in implementing this program. The research employs a qualitative approach with a case study methodology. Data was collected through in-depth interviews with relevant parties, such as the school principal, teachers, and students, as well as direct observations of the entrepreneurship activities carried out at the school. Data analysis was conducted using Spradley’s analysis techniques, which include data reduction, categorization, and the identification of key themes emerging from the interviews and observations. The results show that the entrepreneurship program at SMK NU 2 Kedungpring has been successfully implemented and integrated into project-based learning activities.